A Brief Analysis of The Intertextuality of Mao Zedong's Strategic Issues in Anti-Japanese Guerrilla War in Fundamentals of Guerrilla Warfare: 毛泽东《抗日游击战争的战略问题》在A H. Nasution将军《游击战争基本原则》记载的互文性浅析 - Woro Januarti (Mandarinable: Journal of Chinese Studies, 2025)
This study applies Kristeva's intertextual theory to compare two monumental works written by great Indonesian politicians: Mao Zedong's “Strategic Problems in The Anti-Japanese Guerrilla War” and A H. Nasution's “Fundamentals of Guerrilla Warfare”. Based on Kristiva's theory, this study explores how the book “Strategic Problems in The Anti-Japanese Guerrilla War” influenced A H. Nasution's by analyzing the cultural, geographical, and political differences between China and Indonesia. A H. Nasution wrote “Fundamentals of Guerrilla Warfare” and how General Soedirman led the masses in the guerrilla war against the Netherlands in 1948 under the influence of the book. These two books have had a great influence in the world military field so far, such as “Fundamentals of Guerrilla Warfare” which is still a must read in American military studies. Through the study of these two great works, not only can we understand Mao Zedong and A H. Nasution's profound thoughts have broadened his horizons, and he can also understand the spirit of empathy and the pain of being colonized at that time, as well as how they developed mature political systems and military theories under various controls and conditions of colonialis.